A global analysis of nasopharynx cancer burden attributable to occupational formaldehyde exposure - Li, Jian; Lai, Yongjing; Tang, Anzhou; Yi, Xiang (Frontiers in Oncology, 2025)
BackgroundOccupational formaldehyde is a significant risk factor for nasopharynx cancer. This study aimed to analyze the burden of nasopharynx cancer attributable to occupational formaldehyde using data from the Global Burden of Disease (GBD) 2021.MethodsData on mortality and disability-adjusted life years (DALYs) rates were extracted from the GBD 2021. Joinpoint regression analysis was used to assess trends from 1990 to 2021. Health inequalities were evaluated using the slope index of inequality (SII) and concentration index (CI). An age-period-cohort (APC) model was employed to analyze independent effects, and the Bayesian age-period-cohort (BAPC) model was used to project the disease burden through 2036.ResultsIn 2021, nasopharynx cancer due to occupational formaldehyde exposure had 592.17 deaths (95% uncertainty interval (UI): 401.41 to 856.86) and 25,382.99 DALYs cases globally (95% UI: 16,268.27 to 36,800.17). The highest burden was observed in middle socio-demographic index (SDI) regions (254.25 deaths and 10,692.88 DALYs). East Asia had the highest burden (313.68 deaths and 13,030.97 DALYs cases), while Oceania had the lowest (0.33 deaths). From 1990 to 2021, global age-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR) decreased, although significant increases were observed in the Caribbean and Central Asia. The highest burden was among males aged 45–49 years (88 deaths and 3,869 DALYs cases). Health inequality analysis showed a narrowing gap in DALY rates. A slight increase in nasopharynx cancer burden attributable to occupational formaldehyde exposure is projected by 2036, with a higher burden observed in males than in females.ConclusionsDespite an overall decline in the global burden of nasopharynx cancer attributable to occupational formaldehyde, significant regional disparities persist. Risks associated with gender and age highlight the necessity for enhanced occupational protection and targeted interventions to safeguard high-risk populations. Continued formaldehyde exposure monitoring remains crucial for informing and supporting global cancer prevention strategies.